TiO2 nanowired delivery of cerebrolysin induces superior neuroprotection following exacerbation of blast brain injury pathophysiology in diabetes - Muresanu D.F.; Sharma A.; Lafuente J.V.; Nozari A.; Patnaik R.; Ozkizilcik A.; Tian Z.R.; Mössier H.; Sharma H.S. (My University, 2025)
Military personnel are quite vulnerable to blast brain injury (bBI) during combat operation. The bBI is multiple combination of pressure, rotation, penetration of sharp objects and chemical exposure to barin leading to massive cell and tissue injury. This is quite likely that combat stress alters endocrine regulation and induce diabetes like synptoms. In such cases bBI could further aggravte brain pathology and tissue injury. In this innovation, we demonstrate that a combination of bBI with diabetes (DB) adversely affect brain damage and exacerbates brain pathology. Treatment with cerebrolysin (a multimodal drug comprising neurotrophic factors and active peptide fragments) 30 min to 1 h after bBI (5 to 10 ml/kg, i.v.) significantly reduced brain pathology in normal animals. However, TiO2 nanodelivery of cerebrolysin (5 ml/kg, i.v.) is needed to induce neuroprotection in bBI in diabetic animals. These observations are the first to show that (i) bBI is exacerbated in diabetes, (ii) cerebrolysin has the potential to reduce brain pathology in bBI in healthy animals, whereas, TiO2-nanowired cerebrolysin is needed for neuroprotection in diabetic animals after bBI, not reported earlier. © 2018 OOSV. All rights reserved.